THEORETICAL AND METHODOLOGICAL ASPECTS OF UKRAINIAN TRANSPORT-ROAD COMPLEX RESEARCH - Kudrytska, N. V. (Science and Transport Progress, 2009)
In the article the author’s definition of transport-and-road complex ofUkraineis given, the basic types of transport are characterized. Тhe theoretical-and-methodological aspects of research of transport-and-road complex of Ukrainein the modern economic conditions are formulated.